A Preliminary Qualitative Study of Two Common Acacia Species in Sudan - Ayman Ahmed Jacknoon; Esam. A. Elhefian; Adam Musa Mohammed; Omer Abdalla Ahmed Hamdi; Abdul Hamid Yahaya (E-Journal of Chemistry)
This research is dealing with the analysis of tannins of two common Acacia species of Sudan i.e. Acacia nilotica and Acacia seyal. Bark samples from collections of the two acacia species were extracted with distilled water, 80% methanol and 70% acetone. Two sets of extraction were made, one by boiling, and the other by shaking the samples in the respective solvent for eight hours at room temperature. It was found that the 70% acetone was a more efficient solvent than either water or 80% methanol. In addition, qualitative analysis of the phytochemicals showed that the fruits (garad) contain tannins materials, flavonoids and coumarins.